2015
DOI: 10.3390/atoms3020053
|View full text |Cite
|
Sign up to set email alerts
|

Fully Relativistic Electron Impact Excitation Cross-Section and Polarization for Tungsten Ions

Abstract: Electron impact excitation of highly charged tungsten ions in the framework of a fully relativistic distorted wave approach is considered in this paper. Calculations of electron impact excitation cross-sections for the M-and L-shell transitions in the tungsten ions W n+ (n = 44-66) and polarization of the decay of photons from the excited tungsten ions are briefly reviewed and discussed. New calculations in the wide range of incident electron energies are presented for M-shell transitions in the K-like through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 55 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Using the general-purpose relativistic atomic structure package (GRASP) and the flexible atomic code (FAC), Aggarwal et al [1] calculated excitation energies, radiative rates, and lifetimes for transitions in W 57+ ions [1]. Priti et al [21] reported the electron impact excitation due to 3s 1/2 -3p 3/2 and 3p 1/2 -3d 3/2 transitions in W n+ (n = 44 − 66) ions and magnetic sublevel excitation cross-sections were calculated for the above within the framework of fully relativistic distorted wave approach. Dipti et al [9] considered M-shell electron impact excitation for specific magnetic sublevels in Fe-like W 48+ through Al-like W 61+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Using the general-purpose relativistic atomic structure package (GRASP) and the flexible atomic code (FAC), Aggarwal et al [1] calculated excitation energies, radiative rates, and lifetimes for transitions in W 57+ ions [1]. Priti et al [21] reported the electron impact excitation due to 3s 1/2 -3p 3/2 and 3p 1/2 -3d 3/2 transitions in W n+ (n = 44 − 66) ions and magnetic sublevel excitation cross-sections were calculated for the above within the framework of fully relativistic distorted wave approach. Dipti et al [9] considered M-shell electron impact excitation for specific magnetic sublevels in Fe-like W 48+ through Al-like W 61+ ions.…”
Section: Introductionmentioning
confidence: 99%